Pengaruh Kompres Hangat Dengan Penurunan Keluhan Nyeri Pinggang Ibu Hamil TM III - Wulandari, Dianisa Retno; Astriana, Astriana; Yantina, Yuli; Lathifah, Neneng Siti (MIDWIFERY JOURNAL, 2025)
In the adaptation process, it is not uncommon for mothers to experience discomfort even though it is physiological but still needs to be given a prevention and treatment. Some of the discomforts in the second and third trimesters include frequent urination 50%, vaginal discharge 15%, constipation 40%, flatulence 30%, leg swelling 20%, leg cramps 10%, headache 20%, striae gravidarum 50%, hemorrhoids 60%, 60% shortness of breath and 70% back pain (Astuti, 2009; Ni'amah, 2020). The purpose of the study was to know the effect of warm compresses on reducing low back pain complaints of pregnant women TM III in the Tanjung Bintang Health Center Work Area in 2021.This type of research is quantitative, pre-experimental method with a one group pretest – posttest design approach. The population in this study were pregnant women TM III working area of Tanjung Bintang Public Health Center, 52 people, total sampling technique, data analysis using univariate, and bivariate using dependent t-test experiment.The average low back pain of pregnant women TM III before being given warm compresses in the Tanjung Bintang Health Center Work Area in 2021 for 52 respondents, with a mean of 5.60 standard deviations of 1.159 standard errors of 0.161 and a min-max value of 4-8. The average low back pain for pregnant women TM III after being given warm compresses in the Tanjung Bintang Public Health Center in 2021 for 52 respondents, with a mean of 2.75 standard deviations of 1.186 standard errors of 0.164 and a min-max value of 0-6. The results of the statistical test using the dependent test obtained a p-value of 0.000 (0.05<0.05) which means that there is an effect of warm compresses on reducing low back pain complaints of pregnant women TM III in the Tanjung Bintang Health Center Work Area in 2021. in TM III pregnant women who experience low back pain. Keywords : Warm Compress, Back Pain, Pregnant Women  ABSTRAK Dalam proses adaptasi tidak jarang ibu akan mengalami ketidaknyamanan meskipun hal itu adalah fisiologis namun tetap perlu diberikan suatu pencegahan dan perawatan. Beberapa ketidaknyamanan trimester II dan III diantaranya sering buang air kecil 50%, keputihan 15 %, konstipasi 40%, perut kembung 30%, bengkak pada kaki 20%, kram pada kaki 10%, sakit kepala 20%, striae gravidarum 50%, hemoroid 60%, sesak nafas 60% dan sakit pinggang 70% (Astuti, 2009; Ni’amah, 2020). Tujuan penelitian diketahui pengaruh kompres hangat dengan penurunan keluhan nyeri pinggang ibu hamil TM III di Wilayah Kerja Puskesmas Tanjung Bintang Tahun 2021.Jenis penelitian kuantitatif,  metode pra eksperimen dengan pendekatan one group pretest – posttest design. Populasi dalam penelitian ini adalah ibu hamil TM III Wilayah Kerja Puskesmas Tanjung Bintang, sebanyak 52 orang, teknik sampling total sampling, analisa data menggunakan univariat, dan bivariat menggunakan uji eksperimen t-tes dependen.Rata-rata nyeri pinggang ibu hamil TM III sebelum diberi kompres hangat di Wilayah Kerja Puskesmas Tanjung Bintang Tahun 2021 terhadap 52 responden, dengan mean 5,60 standar deviasi 1,159 standar eror 0,161 dan nilai min-max 4-8. Rata-rata nyeri pinggang ibu hamil TM III sesudah diberi kompres hangat di Wilayah Kerja Puskesmas Tanjung Bintang Tahun 2021 terhadap 52 responden, dengan mean 2,75 standar deviasi 1,186 standar eror 0,164 dan nilai min-max 0-6. Hasil uji statistik menggunakan tes-dependen didapat nilai p-value 0.000 (α<0.05) yang artinya terdapat pengaruh kompres hangat dengan penurunan keluhan nyeri pinggang ibu hamil TM III di Wilayah Kerja Puskesmas Tanjung Bintang Tahun 2021. Dapat diaplikasikan sebagai pertimbangan secara rasional untuk pendekatan pada ibu hamil TM III yang mengalami nyeri pinggang. Kata Kunci : Kompres Hangat, Nyeri Pinggang, Ibu Hamil